Analisis Pelaksanaan Proses Penerimaan dan Penyimpanan Buah-Buahan pada Section Cold Kitchen di PT. Aerofood Indonesia (ACS) Surabaya - M. Daris Athaya Rohmatillah; Asrul Bahar; Ita Fatkhur R; Niken Purwidiani (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
This study aims to analyze the implementation of the fruit receiving and storage process in the cold kitchen section at PT. Aerofood Indonesia (ACS) Surabaya, which is one of the important units in the raw material supply chain in the aviation catering industry. The study used a qualitative descriptive method with data collection techniques through in-depth interviews, direct field observations, and documentation of work procedures. Informants in the study consisted of the Cold Kitchen Supervisor and two staff members who directly handle the fruit receiving and storage activities. The results showed that the fruit receiving process was carried out through three main stages, namely checking documents (delivery orders and purchase orders), physical inspection of the fruit such as color, texture, and aroma, and recording the details of the receipt into a special form. This inspection is important to ensure that the fruit received is in a condition suitable for consumption and in accordance with the established specifications. During the storage stage, the fruit is arranged according to type and level of durability. Small fruits such as strawberries or grapes are stored at a temperature of 0–6°C, while large fruits such as watermelons and melons are stored at a temperature of 18–21°C. This arrangement aims to maintain freshness and extend shelf life. In addition, the FIFO (First In, First Out) system is consistently implemented to prevent the accumulation of old stock that can reduce quality. Storage room temperature monitoring is carried out every 4 hours to ensure temperature stability according to standards. Overall, the implementation of the fruit receiving and storage process at ACS Surabaya has met the principles of good raw material management (Good Reception & Storage Practice). This implementation procedure supports the achievement of quality and food safety standards in flight catering services, which are highly dependent on the timeliness and quality of ingredients.